Accounting Student’s Moral Judgment and Integrated Cultural Religious-Based Ethics Concept - Made Aristia Prayudi; I Putu Hendra Martadinata (Journal of Accounting and Investment, 2020)
Research aims: Despite its widely recognized importance, there is a lack of today's business ethics education regarding the method used for teaching ethics to college students. The conventional business ethics courses are criticized for applying learning approaches limited to the abstract, impersonal moral logic of secular ethics that is less natural, meaningful, and motivating, which cannot have a significant and lasting impact on the moral judgment of its graduates. This current study addresses the issue by investigating the effect of integrating cultural and religious-based ethics concept, named Tri Kaya Parisudha (the Three Holy Deeds—think good, speak good, and do good) into ethical training toward moral judgment development of accounting students.Design/Methodology/Approach: Data were collected from 46 accounting undergraduate students of a large public university in Bali Province of Indonesia by conducting Pre-test-Post-test Control Group experimental design.Research findings: The results showed that participants who were receiving ethical training integrate with the Tri Kaya Parisudha concept (treatment group) exhibited higher moral judgment development (that is, have significantly higher DIT p-score) than those who did not (control group). Besides, there was evidence of a statistically significant increasing DIT p-score in the treatment group from pre to post-test, but not in the control group.Theoretical contribution/Originality: This research contributes to the development of academic studies on Tri Kaya Parisudha and its integration to ethical learning on the development of students’ morality.Practitioner/Policy implication: The results of this study indicate the importance of integrating the value of local wisdom and religiosity values into ethical learning at universities to improve students’ morality.Research limitation/Implication: Although this study found that ethical education at the college level will be more effective if the aspect of religiosity is included within the education process, there are some limitations of this study. First, this study used an experimental method using cases that did not reflect the actual condition and have not been sufficiently related to ethical cases occurring in the business world. Secondly, this study has not been able to fully capture the influence of Tri Kaya Parisudha on students’ behavior. Thirdly, this research did not consider another demographic variable that could affect students’ moral judgment.